Primary Complex Suicide Combining Hanging and Burn a Case Report - Özdemir, Çağlar; Tuğcu, Harun; Asil, Haşim; Din, Hasan (The Bulletin of Legal Medicine, 2006)
The terms ‘complex suicide’ or “combined suicide” are used for the suicide performed by using more than one method of suicide previously planned by the suicidal person to prevent failure of the first method. The synchronal use of a second method to prevent failure of the first method is defined as “primary complex suicide”. Our case is a 25 year-old male who was found in an empty field, on top of a lamppost, burned and was hanged with a chain, two ends locked with a padlock. In his external examination and autopsy, his arms were in boxer position, and there was a furrow slanting upward towards to both mastoid region compliant with the chain and 2nd and 3rd degree burns were on all of the body with partially observed demarcation zone. An ecchymosed fracture was found at the right horn of hyoid bone. There was ecchymosis on the right sternocleidomastoid muscle and around the 4th and 5th cervical vertebrae. It was decided that the case was primary complex suicide with the combination of hanging and burning after all medicolegal investigations. The case was interesting with the combination of scene and autopsy findings.Key words: Primary complex suicide, hanging, self-incineration
Keywords: primary complex suicide; hanging; self-incineration